MODERN PROBLEMS AND INNOVATIVE SOLUTIONS OF THE OIL REFINING INDUSTRY: A NEW APPROACH IN THE ERA OF GLOBAL CHANGES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This in the article oil again work industry in today's global environment current problems , technological transformation processes , carbon neutrality requirements , raw materials of quality decrease , product diversification and energy efficiency issues analysis Statistical information , advanced factories experience , new catalytic processes and innovative integration models based on modern solutions offer Article previously there is scientific from work different accordingly oil again work process new global energy paradigm in the context of analysis does.